INFLUENCE OF HYPOPHTHALMICHTHYS MOLITRIX (VALENCIENNES, 1844) ON CYANOBACTERIAL BLOOM AND ITS SUCCESSION IN WETLAND, INDIA - KUMARI, SUMAN; KARNATAK, G; MISHAL, P; LIANTHUAMLUAIA; BAITHA, RAJU; HASSAN, M A; SWAIN, H S; CHANDRA, GANESH; SARKAR, U K; DAS, B K (Journal of the Inland Fisheries Society of India, 2026)
Cyanophyte-harmful algal blooms (CyanoHABs) are a challenging issue in wetland ecosystems around the world. Cyanobacteria produce microcystins (MCs), which are associated with hepatotoxicity in animals. The seasonal blooms of Microcystis are widely reported in both freshwater and brackish ecosystems throughout the world. The present study aims to address a broader understanding of the seasonality of Microcystis in six wetland ecosystems in Eastern India under different management regimes during 2014-2020. Analysis of water physicochemical parameters such as dissolved oxygen, water temperature, pH, total dissolved solids, Sechi Depth, specific conductivity, total alkalinity, and nutrient parameters (nitrate and phosphate) shows significant (p≤0.05) seasonal variations. The contribution of Microcystis spp. abundance to the total phytoplankton abundance varies from 56 to 96% among the wetlands. The food and feeding habits of H. molitrix were studied, and the same food item present in the same environment was also assessed. Gut content analysis revealed that the dominance of phytoplankton in the gut was higher relative to the water column, and a substantial quantity of phytoplankton, especially Microcystis, was noted. The study also explained the toxicity effect of consumption of microcystins (MCs) on H. molitrix. The food selectivity indices and seasonal blooms of Microcystis spp. suggest H. molitrix is a potential fish species to control algal biomass in wetlands.